EFFECTS OF SINGLE, BINARY AND TERTIARY COMBINATIONS WITH Jatropha gossypifolia AND OTHER PLANT-DERIVED MOLLUSCICIDES ON REPRODUCTION AND SURVIVAL OF THE SNAIL Lymnaea acuminata - Yadav, Ram P.; Singh, Ajay (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
The effect of sub-lethal doses (40% and 80% of LC50/24h) of plant derived molluscicides of singly, binary (1:1) and tertiary (1:1:1) combinations of the Rutin, Ellagic acid, Betulin and taraxerol with J. gossypifolia latex, leaf and stem bark powder extracts and their active component on the reproduction of freshwater snail Lymnaea acuminata have been studied. It was observed that the J. gossypifolia latex, stem bark, individual leaf and their combinations with other plant derived active molluscicidal components caused a significant reduction in fecundity, hatchability and survival of young snails. It is believed that sub-lethal exposure of these molluscicides on snail reproduction is a complex process involving more than one factor in reducing the reproductive capacity.